(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
The Study Centre Edoardo Sanguineti (www.centrosanguineti.unito.it), established at the Department of Humanities of the University of Turin in collaboration with the universities of Genoa, Milan and Salerno, is working to build an extensive and fully navigable archive, configured as a development of Sanguineti’s Wunderkammer, a digital archival database which, over a period of five years, has collected a rich heritage of unpublished, unknown or dispersed documents, partly kept at the Centre and partly in related archives. In order to provide an example of the way in which these acquisitions allow us to approach the study of the author on a new basis, we propose here the analysis of a folder containing six sheets, three handwritten and three typed, found among the papers of the Fondo Eredi Sanguineti: in the three sheets written in biros we find the preparatory material and the various phases of elaboration of the ’Three Green Sonnets’.